World Bank Group Support to Public-Private Partnerships : Lessons from Experience in Client Countries, FY02-12 - Independent Evaluation Group (Washington, DC: World Bank, 2015)
Public-private partnerships (PPPs) are long-term contracts between a private party and a government agency that strive to provide a public asset or service in which the private party bears both some risk and some management responsibility. If implemented well, PPPs can help overcome inadequate infrastructure that constrains economic growth, particularly in developing countries.